The variation of safety pillar’s width with depth under the influence of thermo-mechanical stresses in Underground Coal Gasification - Sakhno, S. V.; Sakhno, I. G.; Bashynskyi, S.; Oidov, M.; Сахно, С. В.; Сахно, І. Г. (University of Zagreb, 2025)
Underground coal gasification is one of the main trends of green mining. The basic principles of underground gasification have been long known. However, the practical implementation of this technology is unfortunately still not widespread. Recently, the Parallel Controlled Retraction Injection Points method has been actively developed, which is the subject of research in this article. An open problem of this technology is the determination of the pillar's width between reactor cavities taking into account the influence of thermo-mechanical destruction of coal. In this study, numerical simulation by ANSYS 17.2 software was used to solve it. The distribution of thermo-mechanical stresses in a coal pillar was studied. Mohr's theory was proposed to predict the destruction of a coal pillar at different depths. It was found that the coal seam failure near the production well and injection well leads to a reduction in the functional width of the safety pillar. Although, contrary to expectations, this effect is not particularly significant. The greater the depth of the seam, the greater the width of the zone of thermo-mechanical destruction of coal in the pillar. In this case, the main reason for the destruction of the coal pillar is the abutment pressure, increased as a result of the collapse of rocks above the gasification cavity in the post-gasification period.
Keywords: underground coal gasification; pillars stability; safety pillar width; thin coal seam gasifiсation; thermal stress